How successful is tree growing for smallholders in the Amazon? - Hoch, L.; Pokorny B.; Jong, W. de (2009)
Growing trees outside forests can generate rural income and rehabilitate degraded lands. The characteristics of existing smallholder tree growing in the Amazon and how much it contributes to livelihoods, however, remains largely unknown. Field surveys in Brazil, Bolivia, Peru and Ecuador were conducted of smallholder tree growing initiatives. Of the studied initiatives, 61% were smallholder initiated and 39% established in donor driven programs. Smallholder schemes generally showed a higher species diversity (85 species) than initiatives in donor driven schemes (52 species). The performance of smallholder tree growing, in terms of growth, health, commercialisation options and contribution to recuperation of degraded areas is limited. Only in 30% of the cases reviewed could smallholders commercialize tree products. Cultivated non-timber forest products had the highest commercialisation rates. The growing of single trees within farm holdings, and the management of natural stands and homegardens showed the highest production efficiencies while depending on minimal inputs.Timber plantations are the least successful. More successful reforestation in the Amazon requires a more realistic view on the limitations of promoting smallholder tree growing, should emphasize non timber products, and better capture local knowledge and experiences